Desain Pengembangan Website dengan Arsitektur Model View Controller pada Framework Laravel - Rahmawati, Levianita; Sumarsono, Sumarsono (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Technological advances have transformed the face of information media from once static to dynamic. The Internet has become a major catalyst in this change, enabling faster and wider access to information. One of the main forms of dynamic information media is the website, which has undergone significant transformation. The use of frameworks in website development is becoming increasingly important to facilitate dynamic accountability to user needs. One of the most popular web frameworks is the Laravel based PHP programming language supported by the Model View Controller architecture. (MVC). The purpose of this study is to present an analysis of how Laravel works in web development, with MVC architecture. The research method used is with the Waterfall Model based on the System Development Life Cycle or SDLC which covers the process of needs analysis through literature studies, system design design-process, design implementation process to program code, system testing process, and system maintenance